Murder most royal - Bennett, Sophia, 1966- (Bennett, Sophia, 1966- Her Majesty the Queen investigates series, 2023)
"Queen Elizabeth II is looking forward to a traditional Christmas gathering with her family in Sandringham when a shocking discovery interrupts holiday plans. A severed hand has been found--but even more unsettling, she recognizes the signet ring still attached to a finger. It belongs to a scion of the St. Cyr family, her old friends from nearby Ladybridge Hall. Despite the personal connection, the Queen wants to leave the investigation to the police--that is, until newspapers drag her name into the matter. As reporters speculate about the proximity of the crime to the Crown and the police fail to investigate a suspicious accident on her doorstep, Elizabeth quietly begins to mull over the mystery herself. With help from her Assistant Private Secretary, Rozie Oshodi, she delves into the interlocking layers of fact and fiction surrounding the high-profile case. Someone in the quiet county of Norfolk seems to have a secret worth killing for, and the Queen is determined to find out who and what that is--even if that means discovering that someone in her close circle is a murderer"--